Genistein ameliorated experimentally induced gastric ulcer in rats via inhibiting gastric tissues fibrosis by modulating Wnt/β-catenin/TGF-β/PKB pathway - Hanan M. Hassan; Nouf M. Alatawi; Alaa Bagalagel; Reem Diri; Ahmad Noor; Deina Almasri; Hussain T. Bakhsh; Hussam I. Kutbi; Noha Ashy; Mohammed M. H. Al-Gayyar (Taylor & Francis Group, 2023)
ABSTRACTObjectives Gastric ulcer (GU) is a prevalent chronic digestive disease affecting about 10% of the world's population leading to gastrointestinal perforation and bleeding. Genistein is a legume flavonoid with antioxidants, anti-inflammatory and antibacterial activities. Therefore, we aimed to investigate the ability of genistein to reduce experimentally induced GU in rats by affecting gastric tissue fibrosis Wnt/β-catenin/TGF-β/SMAD4 pathway.Methods Thirty rats were used. Ten rats served as control, and GU was induced in twenty rats using a single dose of indomethacin (80 mg/kg) orally. Following induction of GU, ten were treated with genistein 25 mg/kg orally. The gastric tissues were isolated to investigate markers of gastric fibrosis, Wnt, β-catenin, transforming growth factor (TGF)-β, SMAD4, and Protein kinase B (PKB). In addition, gastric sections were stained with PAS and anti-TGF-β antibodies.Results Investigation GU micro-images revealed degeneration in both surface cells and glandular epithelial cells, which was improved by genistein. In addition, treatment with genistein significantly reduced the expression of Wnt, β-catenin, TGF-β, SMAD4, and PKB.Conclusion Besides antioxidant activity, genistein improves experimentally induced GU in rats, at least in part, via reduction of gastric tissue fibrosis as indicated by reduction in expression of Wnt, β-catenin, TGF-β, SMAD4, and PKB.